Marketing Development Strategy in the Digital Age - Ibnu Habib; Dean Novansyah; Rendy Dwi Arianto; Hendika Novem Darmawan; Denny Oktavina Radianto (Penerbit Jurnal Indonesia, 2023)
Marketing development strategies in the digital age involve online platforms, digital strategies, and technology-based tools. Technological advancements and internet penetration have promoted their products or services. By using various online platforms and social media, businesses can break through geographical boundaries and increase their brand awareness in different parts of the world. This opens the door to greater business growth and increases the chances of success. Moreover, digital marketing strategies enable more effective targeting. By collecting and analysing user data, businesses can know the interests, preferences and behaviours of their potential audience. This allows them to direct their campaigns with more precision, maximise efficiency, and increase conversion rates.Hopefully, the all-digital development can attract auidens to get info related to the products to be marketed.